Vimentin and cytokeratin expression in nodular hyperplasia and carcinoma of the prostate. Issue 11 (November 1995) - Heatley, M; Maxwell, P; Whiteside, C; Toner, P
Abstract : AIM–To assess the value of vimentin and cytokeratin (CK) intermediate filament proteins (IFPs) in distinguishing between nodular hyperplasia and carcinoma of the prostate and in predicting prognosis in prostatic cancer. METHODS–Fifteen carcinomas and 49 cases of nodular hyperplasia were studied using frozen sections and monoclonal antibodies to CK and vimentin IFPs. RESULTS–There was no statistically significant difference in vimentin expression between nodular hyperplasia and carcinoma. The luminal epithelium in both also reacted with antibodies which detect CK8, 18 and 19. CK 7 expression was found in 57% of cases of nodular hyperplasia and was not identified in any carcinoma. There was a reaction with antibodies to CK1, 2, 3, 4, 10, 11, and 13 in only a minority of cases. There was no statistically significant difference in vimentin and CK reactivity in high and low grade carcinomas. CONCLUSION–Neither vimentin nor CK expression assists in establishing whether a prostatic lesion is benign or malignant or in predicting the biological behaviour of a prostatic carcinoma.